(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Tuberculosis reactivation is one of significant complications after transplantation. Tuberculin skin test (TST) has been the major available screening test in end-stage renal disease patients, but it is associated with a low accuracy. Recently, an interferon-γ release assay (IGRA) has been approved as a substitution test in diagnosis of Mycobacterium tuberculosis infection. This study aimed to compare the ability of the TST and IGRA in the diagnosis of latent tuberculosis in hemodialysis patients and investigate risk factors of having positive test results. Materials and Methods. Forty-seven hemodialysis patients underwent the IGRA and TST tests. Demographic data and blood samples were collected and chest radiography was done for all participants. Result. Abnormal chest radiography was reported in 24% of the study group. The IGRA and TST were positive in 11 (23.4%) and 20 patients (43.5%), respectively. The agreement coefficient (kappa) between the IGRA and TST was 0.31 (P< .05). Positive TSTs were significantly associated with male sex and abnormal chest radiography. Diabetes mellitus was a risk factor for a positive IGRA result (P= .01). Conclusions. The IGRA test is not a sensitive test for detection of latent tuberculosisin hemodialysis patients residing in high-prevalence areas. We suggest that assessment of cellular immunity response in end-stage renal disease patient be a priority before reliance on the IGRA test result.